RAGAM BAHASA DALAM PERCAKAPAN MEDIA SOSIAL DI PLATFORM TIKTOK - Saifani, Yasmin; Muh. Alpan Al-Pansori; Eva Nurmyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Various platforms such as Twitter, Facebook, Instagram, TikTok, blogs, and online discussion forums are used by users from various circles to communicate, share information, and express personal opinions. The popularity of social media not only makes it a means of social interaction but also a linguistic space that displays the diversity of forms and uses of language. Social media, especially TikTok, has become an important linguistic space that displays linguistic diversity according to the user's communication goals, such as entertainment, education, and social campaigns. This study aims to describe the language diversity on TikTok. The data and data sources in this study include primary and secondary data. Data analysis follows the Miles and Huberman model. Data were collected through non-participant observation, documentation with screenshots. The results show that the @aidanmrz account is dominated by a casual style, characterized by the use of everyday vocabulary, abbreviations, and non-standard sentence structures. Meanwhile, the @musfiahsaidah account, which focuses on educational content, uses a more consultative style with a semi-formal character and instructional purpose. These findings suggest that TikTok is a dynamic linguistic space that facilitates the use of a variety of language, from casual to consultative, depending on the context, communication goals, and relationships between speakers.